Study on the Effect of the Use of Bifidobacteria on Flavor of Yoghurt - Suryono .; Adi Sudono; Mirnawati Sudarwanto; Anton Apriyantono (Jurnal Teknologi dan Industri Pangan, 2005)
This experiment was carried out to study the effect of bifidobacteria on flavor of yoghurt. Parameters measured in the experiment were acidity, pH, viscosity, volatile composition, sensory acceptance and intensity of yoghurt sensory attributes. Results of the experiment indicated that the use of bifidobacteria in mixture of yoghurt culture was able to increase the levels of acidity and viscosity of yoghurt. The highest acidity and viscosity was found in yoghurt prepared by Lactobacillus bulgaricus and bifidobacteria mixture, and also by Lactobacillus bulgaricus, Streptococcus thermophilus and bifidobacteria mixture cultures. The major classes of volatile component identified were acids, alcohols, ketones and aldehydes. The major component identified were octanoic acid, acetoin and octadecanal. It was found that there was no significant difference in sensory acceptance of the panelist for colour, aroma and taste of yoghurt prepared by the various combination of cultures. However, consistency of yoghurt prepared by S. thermophilus with or without addition of bifidobacteria, was less compared to that of others. Yoghurt prepared by single culture of S. thermophilus showed higher intensity of bitter and syneresis. The use of bifidobacteria in the cultures mixture decrease the intensity of bitter and syneresis of the yoghurt. Keywords : Bifidobacteria, L. bulgaricus, S. thermophilus, flavor of yoghurt